Ações e percepções ambientais articuladas na sustentabilidade: estudos de múltiplos casos na indústria calçadista - Cultri, Camila do Nascimento [UNESP] (2008)
In the hole world, sustainable development to improve life quality with environment protection is becoming a strong and weel aceptable idea. It is possible to observe that industrial pollution is increasing enviroment and health deterioration, and so, demanding a new attitude from organizations concerning their environment impacts. So, the objective of this paper is to diagnose environmental actions in shoes manufactures, a priori, the importance of local shoes industries in Franca city. So, a theorictical structure was developed based in Environmental Management System, Laws, and Pollution Prevention Programs, each one with a tool, such as ISO 14001, Environmental Licensing and More Clean Production Program. All these elements helped in specific detail in a context that elective actions were studies. The results obtained in the research made us realize that there is a void between benefits presented in the literature about ISO 14001 and real perception of interviewed managers: they just react to avoid legal punishments, wat points the need to keep more rigorous controlson tools such as Environmental Licensing and, at last, it was concluded that More Clean Production Program presented a potential to articulate environment action, applying know-how in private management to public governança, willing to change attitudes to environments improve in shoes supply chain as a hole. So, results of this research identified shy ans incipients actions from interviewed managers to the sustentability of the sector.